The Using of English Songs to Activate Student's Speaking English Skills - Yanti Hidayani Hasibuan; Balqis Wandira; Rafika Dewi Nasution (Talenta Publisher, 2023)
This study's objective was to examine how songs were used to teach speaking proficiency to elementary school kids as well as the issues that teachers ran into. The goal of incorporating the song into all learning phases is to help students become accustomed to the English language's vocabulary and pronunciation by employing an enjoyable method—a song that they are already familiar with. Based on the findings of this study, it can be concluded that the teacher primarily integrated the song into the learning in three activities, such as the opening, while, and closing activities, by providing the students with the link to a YouTube video and assisting them with translation to motivate the students to learn to speak English by using the song. The problem that mostly occurred in the class teaching song for speaking English was not confident in speaking. Because of that, implementing the song for learning English to activate students’ speaking skill.